Non-aversive photographic measurement method for subcutaneous tumours in nude mice. (August 2019) - Resasco, Agustina; Carranza Martin, Ana C; Ayala, Miguel A; Diaz, Silvina L; Carbone, Cecilia
We have developed a new method for the measurement of subcutaneous tumour volume which consists in taking photographs of mice in their home cages, to refine the standard method of measurement with calipers. We consider this new method to be non-aversive, as it may be more compatible with mice behavioural preferences and, therefore, improve their welfare. Photographs are captured when mice voluntarily go into an acrylic tube containing graph paper that is later used as a scale. Tumour volumes measured with the caliper and the non-aversive photographic method were compared to those obtained by water displacement volume and weight. Behavioural and physiological changes were evaluated to assess animal welfare. Significant differences were found between measurements obtained with the caliper and the non-aversive photographic method, v. the reference volume acquired by water displacement ( P < 0.001). Nevertheless, there was good consistency for these measurements when tumours were measured repeatedly, with all Intra-Class Correlation Coefficients above 0.95. Mice on which the non-aversive photographic method was employed were significantly less reluctant to establish contact with the experimenter ( P < 0.001) and behaved less anxiously in a modified-Novelty Suppressed Feeding test. Particularly, statistically significant differences were found in connection with the latency to eat an almond piece ( P < 0.05), the frequency of grooming ( P < 0.001) and the frequency of defecation ( P < 0.001). Corticosterone concentration in faeces and blood glucose were determined and no significant changes were found. Therefore, we propose the non-aversive photographic method to measure subcutaneous tumours as a way to refine methodologies in the field of experimental oncology.